LA TRANSGENERIDAD Y SU EVOLUCIÓN EN EL TRATAMIENTO JURÍDICO BRASILEÑO, SOBRE TODO EN RELACIÓN CON LAS REFLEXIONES TANTO SOBRE LOS DERECHOS DE LA PERSONALIDAD, COMO SOBRE EL PRINCIPIO DE LA DIGNIDAD DE LA PERSONA HUMANA (Functional Plant Breeding Journal, 2022)
The subject of this article is transgenerity and its evolution in the Brazilian legal treatment, especially in what concerns the reflexes both in the personality rights and in the principle of the dignity of the human person. The following problem was investigated: Does the State violate the rights of personality and dignity? The following hypothesis was considered: The State denies rights to transgenders based on binarity. The general objective is the violation of the rights of personality and dignity. The specific objectives exposed are the history and evolution of personality rights. This article is important for a rights operator because it generates a debate beyond sex. For science, it is relevant to perceive the advance beyond gender. For society, it is relevant to point out the injustices experienced by this community. This is a theoretical qualitative research lasting six months.
Keywords: Transgenders. Transsexuals. Transvestites. Name. Rights of personality.